Turning Trouble Around: Re-imagining US Role as Global Player - Lim, Christopher Hang-Kwang (2016)
Donald Trump’s shock election victory has left America divided. However, deep socio-economic challenges exist within the US. Nevertheless, making both America and the world “great again” is not mutually exclusive.